(untitled) (Mustansiria Dental Journal, 2024)
Sixty non-carious extracted human molars were used in this study. The enamel on the occlusal surface ofthe crown of the tooth was removed by a diamond bur then the surfaces of the teeth were ground flat. The teeth were randomly divided into six groups each of ten and stored in distilled water at 370 C. Two types of composite were used in this study, Definite and Tetric. The bonding agents Etch and Prime were prepared according to manufacturers directions and applied to the dentin surface on the first three groups and light cured for 20 seconds. The composite Definite was packed into either 2, 3, and 4mm thick using split metal mould in the first, second and third groups respectively and bulk-cured from top of the composite for 40 seconds, the same procedure was repeated in the remaining three groups but the composite used was Tetric which its corssponding bonding agent was Excite. The bond strength was measured with universal compression machine.The results showed ` that there was no significant difference between the two types of composite Tetric and Definite used in this study. The shear bond strength was affected by the composite thickness, the 2 mm increment showed higher bond strength than the 3mm and 4mm increment in both composites